Neighbors, Drought, and Nitrogen Application Affect the Root Morphological Plasticity of Dalbergia odorifera - Xiang, Li-Shan; Miao, Ling-Feng; Yang, Fan (Frontiers in Plant Science, 2021)
In forest systems, neighbor-induced root morphological plasticity (RMP) is species specific and environment dependent. However, related studies on leguminous woody trees remain sparse. The objectives of this study were to evaluate the root morphological response of the leguminous woody Dalbergia odorifera T. Chen to different N-fixing niche neighbors under models of root system contact and isolation and to evaluate whether such response can be modified by drought or the application of nitrogen (N). The relationship between root morphology and the relative competitiveness of the whole D. odorifera plantlet was also assessed. D. odorifera plantlets from the woody Leguminosae family were used as target species and were grown with either identical N-fixing niche D. odorifera, the heterogeneous but con-leguminous Delonix regia, or the non-leguminous Swietenia mahagoni. All plants were grown under two water conditions (100% and 30% field capacity) and two N treatments (no N application and N application). Two planting models (root system contact in Experiment 1, root system isolation in Experiment 2) were applied to neighboring plantlets. The RMP of D. odorifera was assessed based on root morphology, root system classification, root nodules, and RMP-related indices. The growth of D. odorifera was estimated based on the relative growth ratio, net assimilation rate, and leaf N content. The relative competitiveness of the whole D. odorifera plantlet was evaluated through relative yield. The results of Experiment 1 showed that D. odorifera had different RMP responses to a different N-fixing niche neighbor with root system contact. The RMP of D. odorifera was promoted by a different N-fixing niche neighbor under conditions of drought or N deficiency. Drought improved the RMP of D. odorifera exposed to a different N-fixing niche neighbor. N application converted the promoting effect of D. regia on RMP to an inhibitory effect under well-watered conditions. Experiment 2 showed that belowground interaction with a different N-fixing niche neighbor may be the only way to influence RMP, as effects of aboveground interaction were negligible. Finally, correlation analysis showed that neighbor-induced RMP might predict the relative competitiveness of the whole D. odorifera plantlet under conditions of drought or N deficiency. These findings highlight the influences of neighbors, drought, and N application on the RMP of D. odorifera and contribute to understanding neighbor-induced dynamic changes in the root traits of leguminous woody species in forest systems in the context of climate change.